ANALISIS PEMELIHARAAN MESIN RIDGER PALIR DI PT GREAT GIANT PINEAPPLE - Burhan Nudin (Industrika : Jurnal Ilmiah Teknik Industri, 2018)
The purpose of this study is to determine the optimization of machine maintenance which is applied by the company (companies), the problems that arise in the maintenance system, and the cost of both preventive maintenance and subsequent corrective maintenance activities, to determine the alternatives that is most optimal. The case study will be conducted in the PT Great Giant Pineapple by focusing the research on Ridger Palir machine. The selection will done in this machine, that is to say, considering terms of maintenance, and the high price of the spare parts. Based on the research results that have been done on PT Great Giant Pineapple, the engine maintenance activities, the general implementation of the engine maintenance, shows the company has been running pretty well, but not yet optimal. Out of the problems found in these, the author tried to find a solution by taking into account the cost efficient in carrying out maintenance and engine solutions to the problem of spare part procurement. Preventive maintenance system may be optimal for the efficiency of the company if the determination of the machine preventative maintenance period is predominant. Machine preventative maintenance period can be optimized with the average, that is, the average treatment which cab conducted once every 6 months. Keywords: maintenance, preventive maintenance, corrective maintenance